Color-tuning and boosting circularly polarized luminescence performance of axially chiral tetra-BF2 complexes by post-modifications. Issue 7 (1st February 2023) - Cui, Luxia; Deyama, Koichi; Ichiki, Takafumi; Konishi, Yuto; Horioka, Ami; Harada, Takunori; Ishibashi, Kohei; Hisaeda, Yoshio; Ono, Toshikazu
Abstract : Multicolored fluorescence, high Φ PL reaching 59%, and an efficient g lum up to 0.01 with the brightness for circularly polarized luminescence (125.2 M −1 cm −1 ), were achieved in axially chiral tetra-BF2 complexes by substituent engineering. Abstract : The design and synthesis of novel circularly polarized luminescence (CPL) molecular emitters exhibiting photophysical modulation and high CPL efficiency have become an attractive research topic in synthetic and materials chemistry. In this study, three novel axially chiral tetra-BF2 complexes were rationally designed and synthesized with an easy synthetic approach. The novel terthiophene-substituted tetra-BF2 complexes were successfully prepared by the Suzuki–Miyaura coupling reaction with an isolated yield of 50% using Br-modified precursors. The terthiophene modification affected absorption, fluorescence, and CPL performance by extending the π-conjugation and improving intramolecular charge transfer (ICT) interactions. One compound, terthiophene modified in the meta -position relative to the pyridine moiety of a non-functionalized tetra-BF2 complex, exhibited a yellow-green emission, whereas another compound, terthiophene modified in the para -position, exhibited a yellow emission with a maximum bathochromic shift in both the absorption and emission bands. This is significantly different from unsubstituted and Br-modified compounds, which fluoresced in the green region by the π–π* transition. Moreover, the compound, in which the para -position to the pyridine part in the framework of the tetra-BF2 complex was substituted by terthiophene moieties, exhibited excellent CPL performance with a high dissymmetric factor ( g lum up to the order of 10 −2 ) and CPL brightness ( B CPL ) at 125.2 M −1 cm −1 in toluene owing to the balance of electric and magnetic transition dipole moments compared with those of other tetra-BF2 complexes. This work opens a new avenue for developing novel organic CPL emitters by inducing ICT characters to modulate the emission color and high CPL efficiency.